Optimizing the combustion processes of a small scale solid fuel-fired boiler - Mentes, Dóra; Sajti, Zoltán; Koós, Tamás László; Póliska, Csaba (International Journal of Engineering and Management Sciences, 2019)
Over the last decade, the public has been paying increasing attention to reducing greenhouse gas and acid rain emissions and reducing particulate matter, which is extremely harmful to health and the environment. To improve air quality, the European Commission has achieved a range of measures to reduce air pollutant emissions in the transport, heat and electricity, industrial and agricultural sectors. In Hungary, the amount of gas and solid air pollutants from solid fuel combustion used by the public during the heating season represents a significant percentage of the total amount present in the atmosphere. In 2016, taking into the total emission, the 29% of CO2 emissions; 85% of CO emissions; 75% of the particulate matter emissions and 21% of the NOx emissions were derived from households. It follows that the improvement of air quality can also be achieved by controlling the emissions of solid fuel combustion plants. During our research we aimed to optimize the operation of a newly purchased TOTYA S18 boiler and a pilot pellet boiler. Operating the boilers in the correct mode minimizes air pollutant emissions, and the greater part of the heat generated is actually turns to heating the home, as with poor settings, a lot of heat leaves through the chimney. The data obtained during the tests can also be used to determine whether the boilers comply with the emission values set out in Commission Regulation (EU) 2015/1185.